Beyond `Moneyball`: The rapidly evolving world of sport analytics, part 1 - Alamar, B.; Mehrotra, V. (Analytics, 2011)
Over the past few years, the world of sports has experienced an explosion in the use of analytics. In this three-part series, we reflect on the current state of sports analytics and consider what the future of sports analytics may look like.